UTILIZATION OF RICE HUSK AND LATERITE AS A LOW-COST ADSORBENT FOR HEAVY METAL REMOVAL THROUGH AQUEOUS SOLUTION - SARKALE, PS; JADHAV, AS (Innovare Journal of Agricultural Sciences, 2021)
Objective: Heavy metals are a major pollutant in marine, ground, industrial, and even treated wastewater. Metals are excessively released into the environment due to the natural processes and anthropogenic activities have created a major global concern regarding metal pollution. Hence, there is a strong need for economical and environment-friendly technology. The present study provides the solution for the problem in the form of laterite and rice husk. Methods: The batch method was used to study the adsorption. The batch experiment was performed in two different conditions, stable and shaking. Results: The obtained results from the batch experiment shown the ability of both the adsorbents in removing some heavy metals. Furthermore, it was found that the adsorption of metals by laterite decreases in order of chromium (Cr)>mercury (Hg)>Cadmium (Cd)>lead (Pb) and for rice husk, Hg>Cd>Cr>Pb. Rice husk was found more efficient for removal of Hg, Cd, and Pb. Laterite was more efficient than rice husk for removal of Cr. Conclusion: Therefore, the adsorbents are efficient and cost effective in the treatment of heavy metal contaminated water.